Contributi italiani al XIV Congresso Internazionale degli Slavisti - Alberti, Alberto (Biblioteca di Studi Slavistici, 2008)
This book contains the contributions of the Italian delegation to the XIV International Congress of Slavists (Ocrida, 10-16 September 2008). Divided into three macrosections (Philology and Linguistics; Literature, Culture and Folklore; History of Slavistics) the articles represent the main directions of current research in Slavic studies: from typological linguistics to palaeography, from the problems of intertextuality and multiculturalism to the history of literature, from historic poetics to the analysis of contemporary poetic texts. The book closes with two essays devoted to the reconstruction of several fundamental stages in the early years of Italian Slavistics and the Bibliography of Italian Slavistic production for the period 2003-2007 (edited by Gabriele Mazzitelli), providing eloquent evidence of the lively diffusion and complex ramification of these studies over recent years.